Family practitioners perception of, knowledge about and use of peak flow meters in Lenasia, Lenasia South and Soweto community health centres - Vallabh, Bhadrish Kantilal (My University, 2014)
This study which measures the extent and determinants of peak flow meter use in the management of asthma, is the first to be performed on the topic among South African family practitioners. The study assessed the utilisation of peak flow meters by family practitioners in three highly urbanised areas; compared the method o f utilisation against accepted general guidelines; and it identified the reasons why family practitioners failed to use peak flow meters. A questionnaire was administered to 92.3% (72 of 78) of private and public sector practitioners working in three urban areas of greater Johannesburg. Data were collected concerning practice profiles, characteristics o f the practitioners, the extent o f and indications for use, and the reasons for failure to use these meters. The results showed that only 21 of 72 practitioners (29%) advised their asthmatic patients to use peak flow meters for home monitoring. A scoring system (summary score) which was developed to summarise knowledge of both the indications for the use of meters, and of the method of peak flow measurement showed that only 33,3% of the 72 of practitioners attained maximum or close to maximum scores (6 to 8 o f an 8 point scale). University of undergraduate training and the decade of qualification were associated with the summary score. Cost of the peak flow meter was the most important limiting factor to its use. In conclusion, peak flow meters were under-utilised by family practitioners. Cost of the peak flow meter was an important reported cause of under utilisation. It is recommended that the importance of the peak flow meter in the management o f asthma be emphasised at undergraduate and continuing medical education level,